Remotely detuned receiver coil for high-resolution interventional cardiac magnetic resonance imaging - Marhabaie, Sina; Delcey, Marylène; El Hamrani, Dounia; Vaillant, Fanny; Ginefri, Jean-Christophe; Ozenne, Valéry; Abell, Emma; Poirier-Quinot, Marie; Quesson, Bruno (Frontiers in Cardiovascular Medicine, 2023)
Introduction Interventional cardiac MRI in the context of the treatment of cardiac arrhythmia requires submillimeter image resolution to precisely characterize the cardiac substrate and guide the catheter-based ablation procedure in real-time. Conventional MRI receiver coils positioned on the thorax provide insufficient signal-to-noise ratio (SNR) and spatial selectivity to satisfy these constraints. Methods A small circular MRI receiver coil was developed and evaluated under different experimental conditions, including high-resolution MRI anatomical and thermometric imaging at 1.5 T. From the perspective of developing a therapeutic MR-compatible catheter equipped with a receiver coil, we also propose alternative remote active detuning techniques of the receiver coil using one or two cables. Theoretical details are presented, as well as simulations and experimental validation. Results Anatomical images of the left ventricle at 170 µm in-plane resolution are provided on ex vivo beating heart from swine using a 2 cm circular receiver coil. Taking advantage of the increase of SNR at its vicinity (up to 35 fold compared to conventional receiver coils), real-time MR-temperature imaging can reach an uncertainty below 0.1°C at the submillimetric spatial resolution. Remote active detuning using two cables has similar decoupling efficiency to conventional on-site decoupling, at the cost of an acceptable decrease in the resulting SNR. Discussion This study shows the potential of small dimension surface coils for minimally invasive therapy of cardiac arrhythmia intraoperatively guided by MRI. The proposed remote decoupling approaches may simplify the construction process and reduce the cost of such single-use devices.